Prevalence of central and peripheral neuropathic pain in patients attending pain clinics in Spain: factors related to intensity of pain and quality of life - Failde I (Journal of Pain Research, 2018)
Inmaculada Failde,1,2 María Dueñas,2,3 Maria Victoria Ribera,4 Rafael Gálvez,5 Juan A Mico,2,6,7 Alejandro Salazar,2,3 Helena de Sola,1,2 Concepción Pérez8 1Department of Biomedicine, Biotechnology and Public Health, Faculty of Medicine, University of Cádiz, Cádiz, Spain; 2Institute of Research and Innovation in Biomedical Sciences of the Province of Cadiz, Spain; 3Department of Statistics and Operational Research, Faculty of Sciences, University of Cádiz, Cádiz, Spain; 4Pain Clinic, Hospital Vall d’Hebrón, Barcelona, Spain; 5Pain Clinic, Hospital Virgen de las Nieves, Granada, Spain; 6Department of Neuroscience, Pharmacology and Psychiatry, Faculty of Medicine, University of Cádiz, Cádiz, Spain; 7CIBER of Mental Health, CIBERSAM, Instituto de Salud Carlos III, Madrid, Spain; 8Pain Unit, Hospital de la Princesa, Madrid, Spain Background: The objective of the study was to estimate the prevalence of pure central neuropathic pain (CNP) and peripheral neuropathic pain (PNP) among patients attending pain clinics in Spain. The study also aimed to analyze factors associated with pain intensity and quality of life (QoL). Methods: A cross-sectional study was performed including 53 patients with pure CNP and 281 with pure PNP attending in 104 pain clinics in Spain. The revised grading system proposed in 2008 to determine a definite, probable or possible diagnosis of NP was used. Pain features, psychological variables and QoL were assessed. Descriptive, bivariate and multivariate analyses were performed. Results: The prevalence of pure CNP and PNP amongst neuropathic pain patients was 2.4% (95% CI: 1.7;3.1) and 12.9% (95% CI: 1.5;14.3), respectively. Comorbid anxiety, depression or sleep disorders were high in both groups, but higher in CNP patients (51.1%, 71.4%, respectively). Pain intensity in PNP patients was associated with the presence of depression and sleep disturbances. However, in CNP patients, it was related with pain in the lower limbs. The impairment of QoL was greater in CNP patients than in PNP patients; pain location, presence of depression and sleep disturbance were the factors that most negatively affected QoL. Among PNP patients, women and those with higher pain intensity had worse QoL. Conclusion: Pain intensity and QoL are affected by different factors in patients suffering from CNP or PNP. Identifying these factors could serve to guide therapeutic strategies and improve the QoL of patients. Keywords: central neuropathic pain, peripheral neuropathic pain, pain intensity, quality of life